2019
DOI: 10.1111/ijpp.12521
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of experiential learning in MPharm programmes in UK Universities

Abstract: Objectives To determine the current structure of experiential learning (EL) in Master of Pharmacy (MPharm) programmes in UK universities, and assess how they meet the standards specified by the General Pharmaceutical Council. Methods A cross‐sectional survey of staff in charge of EL in MPharm programmes was conducted, utilising a 31‐item online survey, consisting of both open‐ended and close‐ended questions. Variables of interest were administrative aspects and structure of the EL component, tutor issues and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…11 As such there is variation between the different universities in terms of placement hours, and the structure and governance of EL. 12 Funding depends on each university's resources as well as any external funding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 As such there is variation between the different universities in terms of placement hours, and the structure and governance of EL. 12 Funding depends on each university's resources as well as any external funding.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by respondents in the aforementioned nationwide survey of UK universities, where more than 50% believed that students should receive EL credit for pharmacy employment. 12 There is, however, no stipulation in the Standards which allow students to be excluded from EL because of their part-time work. The School of Pharmacy's philosophy is that all students should have equitable access to EL to enable the School to ensure all students have a similar experience, independent of their part-time work.…”
mentioning
confidence: 99%
“…Pharmacy schools in the United Kingdom offer a wide range of external experiential learning in hospitals, community pharmacies, prisons, care homes, and hospices, but these placements come with the challenges of obtaining and retaining placement providers, quality assurance, and cost. 6 The on-campus HLAs do not replace external placements for pharmacy student, but rather facilitate increased experiential learning in a lowcost, standardized, and quality-assured manner. In 2018, the HLA experience and resources were shared with another UK pharmacy school to support them in piloting student-led health checks.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] A 2018 survey of experiential learning in MPharm programs in the United Kingdom found that the total placement time at each university varies considerably, ranging from nine to 146 hours of community pharmacy placements and 14 to 103 hours of hospital pharmacy placements. 6 Organizing placements for students can be challenging because of increasing class sizes, issues with obtaining and retaining placement providers, and lack of financial support, quality assurance measures, and/or administrative support. 6 In the United States, introductory pharmacy practice experience (IPPE) programs have also experienced challenges such as competition for sites, difficulty conducting site visits, understaffing, and issues surrounding program assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation